2018
DOI: 10.3390/met8110916
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of a High Nb Containing TiAl Alloy with (α2 + γ) Microstructure during Elevated Temperature Deformation

Abstract: In order to verify the correctness of the transition of deformation mechanism with the change in deformation parameters and to reveal the types and mechanism of dynamic recrystallization of γ grains during compression deformation, microstructure characterization of Ti-43.5Al-8Nb-0.2W-0.2B (at. %) alloy after isothermal compression deformation were performed. When the alloy was deformed at 1000 • C/10 −2 s −1 , the initial γ grains are elongated and significantly refined and the fraction of low angle grain boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among a number of TiAl based alloys, TiAl alloys with a (α 2 + γ) microstructure are known to be promising for high-temperature structural materials, such as aero components in air craft. On the Nb-containing TiAl with a (α 2 + γ) microstructure, Chu et al [5] demonstrated that a high temperature deformation mechanism changes the dislocation creep to grain boundary sliding. The editor believes that the characterization of microstructures and the assessment of the deformation mechanism of the relevant alloy should be useful for developing the aero components.…”
Section: Contributionsmentioning
confidence: 99%
“…Among a number of TiAl based alloys, TiAl alloys with a (α 2 + γ) microstructure are known to be promising for high-temperature structural materials, such as aero components in air craft. On the Nb-containing TiAl with a (α 2 + γ) microstructure, Chu et al [5] demonstrated that a high temperature deformation mechanism changes the dislocation creep to grain boundary sliding. The editor believes that the characterization of microstructures and the assessment of the deformation mechanism of the relevant alloy should be useful for developing the aero components.…”
Section: Contributionsmentioning
confidence: 99%
“…Gamma TiAl-based alloys have been successfully applicated in aerospace and automotive industries after decades of developments [1][2][3]. In recent years, TiAl alloys containing a large amount of β-stabilizing elements, such as Nb and Mo, have attracted much more attentions due to their excellent elevated temperature properties [4][5][6][7]. Among them, the TNM alloy, which contains a balanced concentration of Nb and Mo, was recognized as the representative third generation TiAl alloy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As new lightweight and high-temperature structure materials, Ti 2 AlNb alloy and high-Nbcontaining TiAl alloys (abbreviated as TAN alloys) have received significant attention in the aerospace field [1][2][3]. The addition of the Nb element gives them excellent properties, such as low density, high specific strength, favorable oxidation, creep resistance [4], and especially high temperature properties.…”
Section: Introductionmentioning
confidence: 99%